Immunoglobulin E and G autoantibodies against eosinophil proteins in children and adults with asthma and healthy subjects (2023)
ABSTRACT: Background: Autoimmune IgG response has been described in the pathogenesis of asthma in adults, but IgE autoimmunity has been little explored. Considering high levels of blood eosinophils and immunoglobulin E in asthmatic patients, the possibility of IgE autoantibody response to eosinophil proteins arises. Objective: To explore the presence of IgE and IgG autoantibodies against Eosinophil peroxidase (EPX) and Eosinophil cationic protein (ECP). Methods: Three steps were followed: 1) The frequency of IgE and IgG autoantibodies against EPX and ECP was investigated among asthmatic and healthy subjects. 2) The ability of IgE autoantibodies to induce an inflammatory response (basophil activation) was performed. 3) The capacity of autoantibodies to identify patients with severe asthma was evaluated. Results: Asthmatic and healthy subjects had IgE and IgG autoantibodies against EPX and ECP. Anti-EPX IgE was significantly higher in asthmatic patients. Severe asthmatic patients had a higher frequency and higher levels of IgE and IgG autoantibodies compared to healthy subjects. There was not a correlation between autoantibodies and blood eosinophils. Children younger than 14 years of age had IgE and IgG autoantibodies against to EPX and ECP. IgE autoantibodies to EPX and ECP induced basophil activation in asthmatic patients. Conclusion: In this study, we identify for the first time IgE autoantibodies against EPX and ECP in adults and children patients with asthma; IgE and IgG autoantibodies against EPX and ECP could serve as a predictive biomarker of the clinical severity.